Multicomponent Precipitation and Strengthening in Intermetallic-Strengthened Alloys - Fang, J.Y.C.; Liu, W.H.; Yang, T.; Wu, Y.; Jiao, Z.B. (Frontiers in Materials, 2022)
Advanced structural materials with superior mechanical properties are of technological importance for industrial applications. Multicomponent precipitation provides a potential approach for designing high-performance alloys and has been receiving increasing attention from both academia and industry. In this Perspective, we highlight the recent advances and future perspectives in multicomponent-precipitation-strengthened alloys, including multicomponent steels, superalloys, and high-entropy alloys. The emphasis is placed on the unique microstructural features and challenges of multicomponent precipitation as well as their impacts on the strengthening behavior. Finally, future research areas for this class of materials are critically discussed.